Community shifts in a seeded 3‐chlorobenzoate degrading membrane biofilm reactor: indications for involvement of in situ horizontal transfer of the clc ‐element from inoculum to contaminant bacteria - Dirk Springael; Kurt Peys; Annemie Ryngaert; Sandra Van Roy; Liliane Hooyberghs; Roald Ravatn; Marc Heyndrickx; Jan‐Roelof van der Meer; Carlo Vandecasteele; Max Mergeay; Ludo Diels (Environmental Microbiology, 2002)
Summary Pseudomonas putida BN210, carrying the self‐ transferable clc ‐element encoding degradation of 3‐chlorobenzoate on the chromosome, was used as inoculum in different membrane biofilm reactors treating 3‐chlorobenzoate‐contaminated model wastewater. Analysis of the bacterial population in the effluent and in the biofilm showed the loss of BN210 beyond detection from the reactors and the appearance of several novel 3‐chlorobenzoate mineralizing bacteria mainly belonging to the β ‐proteobacteria. In contrast, in non‐inoculated reactors, no 3‐chlorobenzoate degradation was observed and no 3‐chlorobenzoate degraders could be recovered. Southern blots hybridization of genomic DNA using clc ‐element‐specific probes and FIGE analysis indicated the presence of the complete clc ‐element in one or more copies in the isolates. Moreover, the isolates could transfer the clc genes to Ralstonia metallidu‐rans recipients. Two representative reactor isolates, Ralstonia sp. strains KP3 and KP9 demonstrated a higher growth rate on 3‐chlorobenzoate than strain BN210 in batch cultures. When BN210, KP3 and KP9 were simultaneously inoculated in a membrane reactor supplied with 3‐chlorobenzoate, strain KP3 outcompeted the two other strains and remained the major 3‐chlorobenzoate degrading population in the reactor. Our data suggest that in situ horizontal transfer of the clc ‐element from the inoculum to contaminant bacteria in the reactors was involved in the establishment of novel 3‐chlorobenzoate degrading populations that were more competitive under the defined reactor conditions than the inoculum strain.